(untitled) (Stavební obzor - Civil Engineering Journal, 2017)
Over the past couple of decades, root piles as the new tool for addressing a number of tough problems have been gaining a continually increasing interest in tunnel, especially for complex geological conditions. Therefore, in order to promote the development and application of root piles in tunnel engineering, this paper systematically sorts out the research status and development prospect of root piles from the application in foundation underpinning to reinforcement of tunnel foundation. Firstly, the type and development process of root piles are discussed. Secondly, the reinforcement mechanism of the root piles in the tunnel base is refined and combed: the reinforcement mechanism analysis focuses on frictional resistance of soil around pile, soil among piles, and piles. Thirdly, the calculation method of reinforced tunnel foundation is studied from the bearing of vertical load, horizontal load and pile reinforcement design. And through the engineering case, the paper illustrates the reinforcement effect of the root pile in ensuring the stability of the tunnel and the concrete process of the root piles in the tunnel construction. Finally, the problem and development prospect of root piles are discussed, so as to provide new perspectives and fundamental data for the research on tunnel engineering.